2001
DOI: 10.1021/cm010451y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism by Which the Formation of Nanocomposites Enhances Thermal Stability

Abstract: Polystyrene-clay and polystyrene-graphite nanocomposites have been prepared and used to explore the process by which the presence of clay or graphite in a nanocomposite enhances the thermal stability of polymers. This study has been designed to determine if the presence of paramagnetic iron in the matrix can result in radical trapping and thus enhance thermal stability. Nanocomposites were prepared by bulk polymerization using both iron-containing and iron-depleted clays and graphites, and they were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
289
1
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 500 publications
(314 citation statements)
references
References 8 publications
13
289
1
11
Order By: Relevance
“…Second, they can create a network which can protect the polymer from degradation [229][230][231][232]. Third, they can act as radical traps [233]; and lastly, they are capable of altering the microstructure of the product [4,222]. Moreover, strong adhesion between the filler and matrix causes lower mobility of polymer chains followed by reduction of decomposition rate [234,235].…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Second, they can create a network which can protect the polymer from degradation [229][230][231][232]. Third, they can act as radical traps [233]; and lastly, they are capable of altering the microstructure of the product [4,222]. Moreover, strong adhesion between the filler and matrix causes lower mobility of polymer chains followed by reduction of decomposition rate [234,235].…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Polymer-clay nanocomposite materials are reported to promote thermal [48,49], mechanical [50], molecular barriers [51], flame retardant behavior [52][53][54][55][56][57][58][59] and corrosion protection properties [60][61][62]. Therefore, the systematic investigation of the reaction possibility of PAA with synthetic C-S-H at low Ca/Si ratio (0.7) as well as to characterize the composite materials by nanotechnological methods are the main interests of this contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jiao et al [4] reported that EVA/(Mg/Al/Fe-CO3) composites containing a variable amount of Fe 3+ ion obtained a V-0 rating in the UL-94 protocol, while with EVA/MgAl-CO3,(an iron-free hydrotalcite), dripping occurred. The presence of iron as a substitutional impurity in MMT has been shown to lead to radical trapping reactions and a reduction in the PHRR at low amounts of clay [23]. Kong et al have recently reported on a synthetic iron-containing MMT analog and found that the iron has a significant effect on the degradation and fire properties [24].…”
mentioning
confidence: 99%